(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The poultry sector produces chicken meat and eggs, which are the most significant protein sources among livestock foods. The industry is dealing with the effects of climate change, which is creating heat stress and negatively influencing poultry performance and well-being. Heat stress has been the most significant climatic stress confronting the worldwide poultry business, with birds having just a small temperature range when stressed. The purpose of this paper is to determine the effect of heat stress on the performance and well-being of hens. The study examined the research articles of numerous researchers and discovered that high temperature influences poultry performance, nutrition, and health. High temperature decreases feed efficiency, body weight, feed intake, and egg production while increasing the proportion of mortality and the incidence of pathological injuries in poultry fields, which generate major material losses..